Limited pathogenicity and transmissibility of Korean highly pathogenic avian influenza H5N6 clade 2.3.4.4 in ferrets. Issue 4 (19th April 2018) - Noh, J.‐Y.; Lee, D.‐H.; Yuk, S.‐S.; Kwon, J.‐H.; Tseren‐Ochir, E.‐O.; Hong, W.‐T.; Jeong, J.‐H.; Jeong, S.; Song, C.‐S.
Summary: The pathogenicity and transmissibility of a reassortant clade 2.3.4.4 avian influenza A (H5N6) virus were evaluated in ferrets. Virus excretion was detected in the upper respiratory tract, but the ferrets did not show any clinical signs of infection. Transmission did not occur between cohoused or respiratory droplet‐contact ferrets.